APLIKASI SALES FORCE AUTOMATION PT. ASP BREEDING FARM (SFA ASPBF) - Try Septiar Syamfithriani (Sistem Informasi Fakultas Ilmu Komputer Universitas Kuningan, 2018)
The purpose of this research is to analyze and develop a sales force automation application based on website, to help automate sales activities in PT.ASP Breeding Farm. Development of methodology in this research is by the first stage of data collection in the form of interview, observation and literature study. The second stage Analysis and design, analyzing business process sales, business process scheduling, order business process, and data flow diagram. Application development using Content Management Systtem Odoo Version 10. The results achieved on the application of this ASPBF SFA is this application can help sales activities such as, the sales department can record sales transactions and online sales repayment, record customer data. This app assists ASPBF owners in providing bonuses for sales. This application automates sales activities in the form of SFA ASPBF it helps managers and sales / marketing in making a sales schedule well, so that sales opportunities can be utilized. This application can provide a reminder for every sales activity so it can be used to notify the marketing of every activity that must be done Key Word : SFA, Sales, Force, Automation